1995
DOI: 10.1107/s0907444995001569
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and analysis of the subunit assembly and quaternary structure of imidazoleglycerol phosphate dehydratase fromSaccharomyces cerevisiae

Abstract: Imidazoleglycerol phosphate dehydratase (IGPD) from Saccharomyces cerevisiae has been crystallized in the presence of a range of divalent cations using the hanging-drop method of vapour diffusion with ammonium sulfate or polyethylene glycol (PEG) 4000 as the precipitants. X-ray precession photographs have established that the crystals formed with ammonium sulfate (form A) belong to the space group F432, with cell parameter a = 177.5/~ and a single subunit in the asymmetric unit. A preliminary data set collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…4A). A similar situation occurs in yeast IGPD, where crystallographic and solution data indicate a 24-mer of octahedral symmetry (3,13,15,16). The simplest explanation for the biochemical and structural data is that metal coordination sites between trimers are the basis for the formation of a 24-mer and that trimers cannot aggregate to form the 24-mer in absence of metal, even at the high protein concentrations of crystallization.…”
Section: Fig 2 Internal Repeat In Igpdmentioning
confidence: 73%
See 1 more Smart Citation
“…4A). A similar situation occurs in yeast IGPD, where crystallographic and solution data indicate a 24-mer of octahedral symmetry (3,13,15,16). The simplest explanation for the biochemical and structural data is that metal coordination sites between trimers are the basis for the formation of a 24-mer and that trimers cannot aggregate to form the 24-mer in absence of metal, even at the high protein concentrations of crystallization.…”
Section: Fig 2 Internal Repeat In Igpdmentioning
confidence: 73%
“…Aggregation has confounded attempts to obtain a three-dimensional structure for IGPD. Preliminary studies (16) suggested that yeast IGPD crystallized as a 24-mer with molecular octahedral (432) symmetry consistent with its aggregation in solution. However, the cubic crystals diffracted too poorly for structure determination.…”
mentioning
confidence: 97%
“…All IGPD enzymes characterized to date require Mn 2+ for activity (Mano et al, 1993;Tada et al, 1995), and for both the Arabidopsis and S. cerevisiae IGPD proteins it has been demonstrated that this requirement relates to the formation of catalytically active multimeric complexes. Removal of Mn 2+ causes the 24 subunit holoenzyme to dissociate into inactive trimers, while re-addition leads of Mn 2+ leads to reassembly of the active holoenzyme (Mano et al, 1993;Tada et al, 1995;Wilkinson et al, 1995;Glynn et al, 2005). The HISN5A protein has been crystallized and the structure determined to 3.0 Å resolution (Glynn et al, 2005).…”
Section: The Histidine Biosynthetic Pathwaymentioning
confidence: 99%
“…Previous studies on the characterization of IGPD from different species have shown that the apoprotein exists as an inactive trimer but upon addition of manganese (and a limited range of other cations) the trimer assembles further to form a biologically active 24-mer exhibiting 432 symmetry (Hawkes et al, 1995;Tada et al, 1995;Wilkinson et al, 1995). The structure of the trimeric form of the enzyme from the fungus Filobasidiella neoformans has recently been determined (Sinha et al, 2004); however, the absence of bound metals in this structure, the presence of disorder in one of the two histidinerich motifs that have been proposed to be involved in metal binding and catalysis, and the lack of information on the precise mode of subunit assembly prevented a detailed examination of the molecular basis of specificity and catalysis.…”
Section: Introductionmentioning
confidence: 99%